Synthesis and electroluminescence properties of tris-[5-choloro-8-hydroxyquinoline] aluminum Al(5-Clq)3. (June 2015) - Kumar, Rahul; Bhargava, Parag; Srivastava, Ritu; Tyagi, Priyanka
Abstract A new electroluminescent material tris-[5-choloro-8-hydroxyquinoline] aluminum has been synthesized and characterized. Solution of this material Al(5-Clq)3 in toluene showed absorption maxima at 385 nm which was attributed to the moderate energy (π–π*) transitions of the aromatic rings. The photoluminescence spectrum of Al(5-Clq)3 in toluene solution showed a peak at 522 nm. This material shows thermal stability up to 400 °C. The structure of the device is ITO/0.4 wt%F4-TCNQ doped α-NPD (35 nm) / Al(5-Clq)3 (30 nm) / BCP (6 nm) / Alq3 (30 nm) / LiF (1 nm) / Al (150 nm). This device exhibited a luminescence peak at 585 nm (CIE coordinates, x = 0.39, y = 0.50). The maximum luminescence of the device was 920 Cd/m2 at 25 V. The maximum current efficiency of OLED was 0.27 Cd/A at 20 V and maximum power efficiency was 0.04 lm/W at 18 V.